Paraoxonase-1 Q192R polymorphism and its association with hs-CRP and fasting blood glucose levels and risk of coronary artery disease. Issue 2 (March 2019) - Amini, Mahsa; Esmaeilzadeh-bahabadi, Sedigheh; Avan, Amir; Gholoobi, Aida; Ghasemi, Faezeh; Mirhafez, Seyed Reza; Ghazizadeh, Hamideh; Moohebati, Mohsen; Ebrahimi, Mahmoud; Ferns, Gordon A.; Pasdar, Alireza; Mobarhan, Majid Ghayour
Abstract: Aims: Paraoxonase-1 (PON1) has been shown to protect low-density lipoprotein cholesterol (LDL-C) and high-density lipoprotein cholesterol (HDL-C) against oxidative-modification and thereby might protect against coronary-artery-disease (CAD). Here we explored the relationship of a genetic variant (a substitution (R) Arg with (Q) Gln at position 192) of PON1 in 250 patients with/without CAD. Materials and methods: Genotyping of PON1 Q192R was carried out using Real-Time-PCR TaqMan-based-probe. Demographic-characteristics and biochemical-analyses, including fasting blood sugar (FBS), HDL, LDL, triglycerides (TG) and C-reactive protein (CRP) were evaluated. Univariate/multivariate analyses were performed to determine the association of the genetic polymorphism and CAD as well as with clinical-characteristics of population. Results: Our findings showed that RR-genotype was more frequent in CAD-patients, compared to the wild-type genotype. Moreover, CAD patients with RR-genotype had an odd ratio of 5.0 (95% CI: 1.3–18.6; p = 0.017), versus wild-type genotype, in multivariate-analysis. Of note we also observed that CAD-patients with QQ-genotype had a significantly lower Hs-CRP level, compared to the RR-genotype. Conclusion: we demonstrate that PON1-Q192R-polymorphism was associated with CRP and FBS levels; R-allele of PON1-Q192R may be an independent risk factor for CAD. Further studies are warranted to determine the value of this marker as a surrogate marker in CAD patients.